2017
DOI: 10.1002/14651858.cd007759.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Manipulative interventions for reducing pulled elbow in young children

Abstract: BackgroundPulled elbow (nursemaid's elbow) is a common injury in young children. It often results from a sudden pull on the arm, usually by an adult or taller person, which pulls the radius through the annular ligament, resulting in subluxation (partial dislocation) of the radial head. It can also be caused by a fall or twist. The child experiences sudden acute pain and loss of function in the affected arm. Pulled elbow is usually treated by manual reduction of the subluxed radial head. Various manoeuvres can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
2
10
0
1
Order By: Relevance
“…12 In most of the studies, girls have been found more affected than boys. 13,14 Similarly, in our study, most patients with pulled elbow occurred in female children 71.9%. It is not clear why it is common in female children.…”
Section: Discussionsupporting
confidence: 75%
“…12 In most of the studies, girls have been found more affected than boys. 13,14 Similarly, in our study, most patients with pulled elbow occurred in female children 71.9%. It is not clear why it is common in female children.…”
Section: Discussionsupporting
confidence: 75%
“…Several studies have compared both manoeuvres and showed that the hyperpronation manoeuvre is less painful 12 and has a higher success rate for reduction, 6 although their results remain inconclusive 13 …”
Section: Figurementioning
confidence: 99%
“…Several studies have compared both manoeuvres and showed that the hyperpronation manoeuvre is less painful 12 and has a higher success rate for reduction, 6 although their results remain inconclusive. 13 This can be explained as follows. The hyperpronation manoeuvre is a direct reduction way that pulls up the trapped supinator muscle and annular ligament from the joint.…”
mentioning
confidence: 99%
“…По его данным, при применении гиперпронационного метода удельный вес неудач первой попытки репозиции варьировал от 4,4 до 20,6 % (средние показатели -9,2 %), а при использовании супинационнофлексионного -от 16,2 до 34,2 % (средние показатели -26,4 %). При гиперпронационном методе отмечен существенно более низкий удельный вес неудачных попыток репозиции (отношение рисков (ОР) -0,53 %; ДИ 0,32-0,87 %) [42]. В последнем из опубликованных рандомизированных контролируемых исследований, в которое вошли 116 пациентов и которое не было учтено в упомянутых выше обзорах, гиперпронационный метод также признан более эффективным, чем супинационно-флексионный: репозиция с первой попытки достигнута у 85 против 53 % пациентов, со второй попытки -у 50 против 28 % пациентов.…”
Section: лечениеunclassified